Teachers’ Experience of Using ICT in the Community Schools - Phunyal, Bal Krishna (GS Spark: Journal of Applied Academic Discourse, 2024)
This article examines the teachers’ experiences of using ICT in teaching and learning in a community school in Nepal. Most teaching and learning processes increasingly depend on technology, and this study discusses the theoretical issues of integrating technology into the classroom. To investigate the major challenges and opportunities of using ICT tools and techniques in a community school in Nepal. The data or information is gathered through online and face-to-face moods of a semi-structured interview. The results showed more opportunities than challenges or issues in the ICT-integrated teaching and learning process. It also presents that insufficient information and communication technology (ICT) knowledge and skills, unstable internet services, lack of electrical power, lack of proper administrative support, and other factors directly influence the proper use of ICT integrated learning in community schools. Moreover, the teachers, students, and other stakeholders have the knowledge and skills of digital literacy. Integrating ICT into teaching and learning activities ensures that they are more effective and purposeful, making the process both applicable and practical.